Evaluation of fluorescent pseudomonads for the management of sheath rot of rice - Sundaramoorthy M (Department of Plant Pathology, College of Agriculture, 2004)
The study entitled ‘Evaluation of fluorescent pseudomonads for the management of sheath rot of rice’ was carried out at three stages i.e., under in vitro condition, green house condition, and field conditions. First two were conducted at the college of Agriculture, Vellayani, and the third one was conducted at CSRC, Karamana. The pathogen Sarocladium oryzae was isolated from the sheath portion of naturally infected rice plants and its identity was confirmed based on the cultural and morphological studies. Twenty different isolates of fluorescent pseudomonads were isolated from, rhizosphere and phyllosphere of healthy rice plants collected from various locations of southern Kerala. They were screened against Sarocladium oryzae under laboratory condition following duel culture technique. Based on the inhibition zone formation six best isolates were selected. In green house studies, six selected isolates were made into a talc based formulation and applied as seed treatment, seedling root dip and foliar spray. Here, the isolate Pf 16 performed well over other isolates and proceeded further for study under field condition. In the field, powder based formulation of selected isolate Pf16 in three different methods of application viz., seed treatment (ST), seedling root dip (SRD) and foliar spray (FS) in nine combinations were applied. Among the different combinations tried combined application of seed treatment + seedling root dip + foliar spray (ST+SRD+FS) gave considerable reduction in disease incidence and improved biomass yield. Based on the preliminary biochemical studies conducted the isolates Pf16, Pf19 and Pf8 were tentatively identified as Pseudomonas fluorescens biovar II, Pseudomonas aeruginosa, Pseudomonas fluorescens biovar I respectively. The metabolite of promising isolate Pf16 extracted and it formed a clear inhibition zone around the pathogen when antagonism was done.